THE INFLUENCE OF ENVIRONMENTAL DYNAMISM, DYNAMICS CAPABILITY, AND FINANCIAL LITERACY ON THE PERFORMANCE OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN MAKASSAR CITY - Aswar, Nurul Fadilah; Aslam, Annisa Paramaswary; Wulansary, Ilma; Hamka, Rezky Amaliah; Abadi, Rahmat Riwayat (Transpublika Publisher, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are crucial for the Indonesian economy, especially in Makassar. They contribute significantly to economic activities and public income. According to data from the Makassar City Cooperatives and MSMEs Office in 2021, there are 4,816 registered MSMEs in various sectors such as trade, industry, non-industrial, and others. The trade sector, including fashion and culinary, is particularly dominant in Makassar. However, the performance of MSMEs has experienced a decline. This study focuses on exploring the factors that affect their performance, specifically environmental dynamism, which encompasses environmental changes, government regulations, shifts in consumer demand, innovation, and technology. The adaptability of MSMEs to these environmental changes is a crucial aspect of their performance. Additionally, financial literacy also plays a significant role in improving their performance. The study aims to investigate the influence of environmental dynamism, adaptability, and financial literacy on the performance of MSMEs in Makassar. The research method employed is quantitative, involving interviews, questionnaires, and observations of 100 MSMEs in the trade sector. The research findings indicate that environmental dynamism and financial literacy have a significant impact on the performance of MSMEs, whereas adaptability does not show the same level of significance. Furthermore, the study highlights the importance of financial literacy in the financial management and decision-making processes of MSMEs. This research provides valuable insights into the factors that influence the performance of MSMEs and offers relevant recommendations to enhance the sustainability of the MSME sector in Makassar.